Unrecognized fluid overload during induction therapy increases morbidity in patients with acute promyelocytic leukemia. Issue 18 (31st May 2019) - Chamoun, Kamal; Kantarjian, Hagop M.; Wang, Xuemei; Naqvi, Kiran; Aung, Fleur; Garcia‐Manero, Guillermo; Borthakur, Gautam; Jabbour, Elias; Kadia, Tapan; Daver, Naval; DiNardo, Courtney D.; Jain, Nitin; et al.
Abstract : Background: The combination of all‐trans retinoic acid (ATRA) and arsenic trioxide (ATO) has proven to be the most effective therapy for patients with acute promyelocytic leukemia (APL). The majority of the morbidity and mortality from APL therapy occur during the induction phase. The objective of the current study was to identify the risk factors associated with transfer to the intensive care unit (ICU) and endotracheal intubation during induction therapy in patients with APL. Methods: The authors analyzed the clinical characteristics of 187 patients with newly diagnosed APL who were treated with ATRA and ATO with or without gemtuzumab ozogamicin. The authors documented the percentage change in body weight from baseline to the maximum recorded weight during induction or to the day of ICU transfer. Results: A total of 18 patients (10%) who initiated therapy with ATRA and ATO on a regular hospital floor required transfer to the ICU after a median of 12 days of induction therapy. The median volume of transfusions was 4350 mL (range, 60‐30, 750 mL). The volume of transfusions was the main factor associated with the risk of ICU transfer (odds ratio, 4.1; P  < .001). Of the 18 patients transferred to the ICU, 10 patients (5%) required intubation. An increase in the total volume of transfusions, increase in weight ≥10% during induction therapy, and a plasma albumin level ≤3.2 g/dL at the time of diagnosis were found to be associated with an increased risk of endotracheal intubation. Conclusions: Large volumes of blood product transfusions and unrecognized fluid overload during induction are associated with ICU transfer and endotracheal intubation in patients with APL. These can be prevented by limiting the amount of transfusions, careful monitoring for subtle signs of fluid overload, and early intervention with aggressive diuretic therapy. Abstract : Fluid overload is a significant complication that is associated with an increased risk of intensive care unit (ICU) transfer and intubation in patients with acute promyelocytic leukemia who are receiving induction therapy. In the current study, the authors attempt to identify the risk factors associated with ICU transfer and endotracheal intubation in these patients.